Effect of Firm Size Firm Growth Firm Age and Independent Commissioner on Intellectual Capital Disclosure in Banking Companies Listed on the Indonesia Stock Exchange in the period 2014 – 2018: Pengaruh Firm Size Firm Growth Firm Age dan Independent Commissioner terhadap Intellectual Capital Disclousure pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia pada periode 2014 – 2018 - Lailatul Khosi'ah; Sriyono (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of the study was to determine and analyze the effect of Firm Size, Firm Growth, Firm Age and Independent Commissioner on Intellectual Capital Disclousure partially and simultaneously to determine a model that can be used to measure Intellectual Capital Disclousure in companies by using panel data regression in Registered Banking companies on the Indonesia Stock Exchange. This study applies quantitative method and the object of this research is done by population and sample randomly (purposive sampling), which are 11 consumer goods companies that were Listed on the Indonesia Stock Exchange in the period 2014 - 2018. The technique of collecting data used annual financial statements from the period 2014 - 2018 and analysis used panel data regression method with common model approach using Eviews 9 program.The results of this study showed that simultaneously and partially variables Firm Size, Firm Growth, Firm Age and Independent Commissioner have a significant effect on Intellectual Capital Disclousure